Effect of thermal treatment on the antioxidant ability of black garlic produced from Phan Rang’s natural fresh material - Nguyen, Nguyen Thi; Hoa, Phan Ngoc; Thao, Le Thi Thu; Tuan, Phan Dinh (Vietnam Journal of Science and Technology, 2017)
Black garlic is a product from the natural fresh garlic, produced by maturing in an environment of enough moisture for a long period. Black garlic contains phenolic, flavonoid and much higher antioxidant activity than that of the natural one. This study is aiming at determining the influence of maturing temperature and retention time to the transformation of the natural fresh garlic into the black one. Influence of moisture, pH, concentration of phenolic, flavonoid, antioxidant activity and the organoleptic properties of the black garlic were investigated at the temperatures of 60, 70, 80 °C during the incubation period of 10, 20, 30 and 40 days. It was shown that moisture and pH decrease while handling temperature increasing and prolonged incubation period. The content of amino acid, phenolic compounds, flavonoids reached their highest values of 5.752 mg/g, 8534 μg GAE/g dry matter and 492.41 μg GE/g dry matters, correlatively, at the temperature of 60 °C in 30 days. The antioxidant activity determined by DPPH technique as well as the reduction capacity got the highest value at the temperature of 60 °C in the incubation period of 30 days. In comparition with raw fresh garlic, the black onec incubated at 60 °C in 30 days has super high phenolic components, flavonoids as well as the antioxidant activity. The produced black garlic is of soft structure, no pungent smell, sweet and sour tastes, appropriate for regular use.